On the influence of grouping practices on classroom teaching - (:unkn) unknown (My University, 2005)
The article starts with a historical overview, discusses the arguments for and against ability grouping. It surveys the literature on different practices of grouping that exist in the American and British literature. The study mainly focuses on instructional grouping practices based on ability and on cooperation. It discusses arguments for and against ability grouping. The study also presents information about the use of mastery learning with cooperative strategies.